DEVELOPMENT OF DATA WAREHOUSE TO PREDICATE THE REGARDING OF UMROH CONGREGATIONS USING THE MANEAREST NEIGHBOUR ALGORITHM (CASE STUDY PT. BAHANA SUKSES SEJAHTERA) - Akhmad Wijaya Kusuma; Deni Mahdiana (Jurnal Teknik Informatika (Jutif), 2022)
Bahana Sukses Sejahtera is a travel company whose one goal is to serve Umrah activities to the holy land of Mecca, Saudi Arabia. The company has been carrying out travel activities for 15 years. Interest from travel activities, especially with the aim of Umrah to the holy land of Mecca from year to year is increasing because the economic conditions of prospective pilgrims are getting better. More and more Umrah travel enthusiasts certainly create abundant data but of course if not processed properly the data will not produce good information. How to get good information with good data processing so that information can be used as knowledge for company decision making. The activity of utilizing big data into information is to use information technology and databases and then design a data warehouse. Data warehouse design and data mining is the most effective technique to produce information that has knowledge for corporate decision making. The knowledge generated from the data warehouse is that one of them can produce information to predict prospective Umrah travel pilgrims who may be canceled due to something that makes it impossible to leave. One of the algorithms used for the predicting process can use the nearest neighbor algorithm. The results of the algorithm can produce predictive information about factors that are very influential on the cancellation of the departure of prospective Umrah pilgrims, for example due to family reasons. Based on this explanation, this research was developed by utilizing information technology and software to make predictive analysis based on existing data regarding the cancellation of the departure of Umrah pilgrims at the travel company PT. Bahana Sukses Sejahtera.